Flexural performance of beams strengthened with a strain-hardening cementitious composite overlay - M. Iqbal Khan; S. Umer Sial; Galal Fares; Mohamed ElGawady; Shehab Mourad; Yousef Alharbi (Case Studies in Construction Materials, 2022)
Strain-hardening cementitious composites (SHCC) improve the performance of tensile properties and crack control. In this investigation, SHCC formulated based on desert sand could be used to strengthen structural members by improving their load-carrying capacity and controlling the cracking system. This work focuses on the efficient strengthening of reinforced concrete (RC) beams using the formulated SHCC overlays for improved performance. First, an SHCC mix with improved tensile and flexure properties was prepared. In addition, two SHCC overlays with reinforcement levels of 0% and 0.4% were developed and applied on RC beams. Eight full-scale beams were prepared and tested through a 4-point bending test. The results showed that SHCC overlay beams enhanced the flexural capacity, ductility, and controlled the crack widths in the beams. In contrast to the reference beams and the SHCC-enhanced beams, the SHCC layer's presence decreased the crack opening by 23–66%. Among the overlay beams, the beam reinforced with an SHCC overlay of a thickness of 30% was found to be the most efficient in terms of crack control and flexural performance. A theoretical procedure was employed to predict the flexural response of beams. The analytical model applied in this investigation could capture the performance of the test specimens. It predicts 0.85–1.34 of the experimental cracking moments with an average of 1.03 and a standard deviation of 0.21, as well as 1.02–1.06 of the yielding moments with an average of 1.03 and experimental standard deviations of 0.02. The average of the difference between the composite beams' predictive and experimental moment capacities is less than 10%. The SHCC mix formulated based on desert sand can be efficiently used in retrofitting applications.